Post-invasion events after infection with Staphylococcus aureus are strongly dependent on both the host cell type and the infecting S. aureus strain. (September 2016) - Strobel, M.; Pförtner, H.; Tuchscherr, L.; Völker, U.; Schmidt, F.; Kramko, N.; Schnittler, H.-J.; Fraunholz, M.J.; Löffler, B.; Peters, G.; Niemann, S.
Abstract: Host cell invasion is a major feature of Staphylococcus aureus and contributes to infection development. The intracellular metabolically active bacteria can induce host cell activation and death but they can also persist for long time periods. In this study a comparative analysis was performed of different well-characterized S. aureus strains in their interaction with a variety of host cell types. Staphylococcus aureus (strains 6850, USA300, LS1, SH1000, Cowan1) invasion was compared in different human cell types (epithelial and endothelial cells, keratinocytes, fibroblasts, osteoblasts). The number of intracellular bacteria was determined, cell inflammation was investigated, as well as cell death and phagosomal escape of bacteria. To explain strain-dependent differences in the secretome, a proteomic approach was used. Barrier cells took up high amounts of bacteria and were killed by aggressive strains. These strains expressed high levels of toxins, and possessed the ability to escape from phagolysosomes. Osteoblasts and keratinocytes ingested less bacteria, and were not killed, even though the primary osteoblasts were strongly activated by S. aureus. In all cell types S. aureus was able to persist. Strong differences in uptake, cytotoxicity, and inflammatory response were observed between primary cells and their corresponding cell lines, demonstrating that cell lines reflect only partially the functions and physiology of primary cells. This study provides a contribution for a better understanding of the pathomechanisms of S. aureus infections. The proteomic data provide important basic knowledge on strains commonly used in the analysis of S. aureus -host cell interaction.